Enhancement of magnetoresistance characteristics in spin valve structures by two-step sputter deposition - Park, CM; Shin, KH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1998)
Spin valve structures were prepared by two-step deposition procedures. Upper layers were deposited at a higher sputtering pressure, while lower layers were deposited at a lower pressure. The possibility of independent control of maximum magnetoresistance and interlayer coupling was found. By employing the procedure, for example, two samples with similar magnetoresistance but quite different coupling fields (CF) can be produced. One has MRmax 4.0 %, CF = 7.6 Oe and the other has MRmax = 4.1 %, CF = 15.5 Oe. It is thought that the two-step-deposited samples combine reduced current shunting dud to the high pressure growth and reduced ferromagnetic interlayer coupling due to the low pressure growth.
Keywords: MULTILAYERS